Adherence to NICE guidance on lifestyle advice for people with schizophrenia: A survey. (June 2017) - Swaby, Lizzie; Hind, Daniel; Gossage-Worrall, Rebecca; Shiers, David; Mitchell, Jonathan; Holt, Richard I. G.
Abstract : Aims and method: The STEPWISE trial (STructured lifestyle Education for People WIth SchizophrEnia, schizoaffective disorder and first episode psychosis) is currently evaluating a lifestyle education programme in addition to usual care. However, it is difficult to define what constitutes 'usual care'. We aimed to define 'usual care' for lifestyle management in people with schizophrenia, schizoaffective disorder and first-episode psychosis in STEPWISE study sites. Ten National Health Service (NHS) mental health trusts participated in a bespoke survey based on the National Institute for Health and Care Excellence (NICE) guidance. Results: Eight trusts reported offering lifestyle education programmes and nine offered smoking cessation support. Reported recording of biomedical measures varied. Clinical implications: Although recommended by NICE, lifestyle education programmes are not consistently offered across UK NHS mental health trusts. This highlights missed opportunities to improve the physical health of people with psychotic illness. Our survey benchmarks 'usual care' for the STEPWISE study, against which changes can be measured. Furthermore, future studies will be able to identify whether any progress in clinical practice has been made towards achieving the NICE recommendations.